2023
DOI: 10.1038/s41598-023-31995-w
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis, antioxidant activity, docking simulation, and DFT analysis of different heterocyclic compounds

Abstract: In this investigation, pressure microwave irradiation was used to clarify the activity of 1-(2-hydroxyphenyl)-3-(4-methylphenyl)prop-2-en-1-one (3) towards several active methylene derivatives utilized the pressurized microwave irradiation as green energy resource . Chalcone 3 was allowed to react with ethyl cyanoacetate, acetylacetone, and thioglycolic acid; respectively, at 70 °C with pressure under microwave reaction condition to afford the corresponding 2-hydroxyphenylcyanopyridone, 2-hydroxyphenyl acetylc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 63 publications
2
9
0
Order By: Relevance
“…Practicing chemists generate EPMs from experimental data and use the resulting model to detect high reactivity within a molecule. Examples of this are included in the popular journal Nature in which several articles were published using EPMs during the year this paper was written (Jain et al, 2023;Kang et al, 2023;Shalaby et al, 2023). Being able to interpret and utilize EPMs is becoming an essential skill of a practicing chemist and should be considered as a part of student training.…”
Section: Discussionmentioning
confidence: 99%
“…Practicing chemists generate EPMs from experimental data and use the resulting model to detect high reactivity within a molecule. Examples of this are included in the popular journal Nature in which several articles were published using EPMs during the year this paper was written (Jain et al, 2023;Kang et al, 2023;Shalaby et al, 2023). Being able to interpret and utilize EPMs is becoming an essential skill of a practicing chemist and should be considered as a part of student training.…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate the antioxidant potential of the newly synthesized compounds (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), their radical-scavenging capacities were determined using the 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) assay. [31] This method is based on the ability of the DPPH radical to abstract H-atoms from antioxidants (AÀ H) to form the hydrazine derivative DPPHÀ H Figure 1, as depicted in reaction 1.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…A wide range of pharmacological applications has been reported for chalcone derivatives incorporating a heterocyclic scaffold, which includes antioxidant, antibacterial, anticancer, antiplatelet, and anti-inflammatory activities. [6][7][8][9][10][11] Among these properties, the antioxidant properties of chalcone derivatives have been extensively investigated. [12] It is reported that chalcones with proper functional substituents (e. g., OH or NH) can exhibit a great efficacy in antioxidant activity due to their potent abilities to scavenge ROS directly through hydrogen or electron transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from heterocyclic synthesis, metal-mediated chemistry, and industrial preparation of aromatic compounds using microwaves, this technology has been extended to continuous-flow organic synthesis also. Lastly the wide application of microwaves in organic synthesis can enhance its value for the synthesis of high-value organic chemicals, polymers, and nanomaterials in much less time than would be required using conventional heating methods . Recently, Szostak and his group reviewed the synthesis of privileged heterocyclic moieties which could be amenable to microwave irradiation also …”
Section: Introductionmentioning
confidence: 99%